Imaging based body composition profiling and outcomes after oncologic liver surgery - Bernardi, Lorenzo; Roesel, Raffaello; Vagelli, Filippo; Majno-Hurst, Pietro; Cristaudi, Alessandra (Frontiers in Oncology, 2022)
Body composition profiling is gaining attention as a pre-operative factor that can play a role in predicting the short- and long- term outcomes of patients undergoing oncologic liver surgery. Existing evidence is mostly limited to retrospective and single-institution series and in many of these studies, the evaluation of body composition is based on parameters which are derived from CT-scan imaging. Among body composition phenotypes, sarcopenia is the most well studied but this is only one of the possible profiles which can impact the outcomes of oncologic hepatic surgery. Interest has recently grown in studying the effect of sarcopenic obesity, central obesity, or visceral fat amount, myosteatosis, and bone mineral density on such patients. The objective of this review is to summarize the current evidence on whether imaging-based parameters of body composition have an impact on the outcome of patients undergoing liver surgery for each of the most frequent indications for liver resection in clinical practice: hepatocellular carcinoma (HCC), cholangiocarcinoma (CCA), and colorectal liver metastases (CRLM).